The Intensity of Cyberactivism in Building Supportive Politics in 2024 - Hasanah, Naomi Ainun; Budiarti, Erlita (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
The year 2024 will be an important year in political history for many countries around the world. The general elections scheduled for that year will bring a variety of changes, challenges, and opportunities to politics. However, one element that is becoming increasingly important in the build-up to these elections is the role of intense cyberactivism in shaping supportive and inclusive politics. In recent decades, the intensity of cyber activism has become increasingly significant in influencing the course of politics. Online activists have the ability to quickly spread messages to a wide audience, organize effective online campaigns, and shape public opinion. This study aims to understand how the intensity of cyberactivism affects political dynamics in preparation for the 2024 general election. The descriptive qualitative method is used as a procedure to analyze the problem with the aim of providing an accurate description of the current situation, with a focus on in-depth interviews and content analysis. The results show that the intensity of cyberactivism plays a significant role in shaping supportive politics ahead of the 2024 general election. Online activists have the ability to influence policy change, mobilize the masses, and accelerate changes in public opinion. They use various strategies, such as hashtag campaigns, online petitions, and the creation of engaging content, to achieve their goals. Content analysis also reveals the complexity of the various political messages spread by online activists. The impact of these messages on public opinion evolves dynamically, depending on the context and community response.